1.03(1.24)(5-x)=6

Simple and best practice solution for 1.03(1.24)(5-x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.03(1.24)(5-x)=6 equation:


Simplifying
1.03(1.24)(5 + -1x) = 6

Multiply 1.03 * 1.24
1.2772(5 + -1x) = 6
(5 * 1.2772 + -1x * 1.2772) = 6
(6.386 + -1.2772x) = 6

Solving
6.386 + -1.2772x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6.386' to each side of the equation.
6.386 + -6.386 + -1.2772x = 6 + -6.386

Combine like terms: 6.386 + -6.386 = 0.000
0.000 + -1.2772x = 6 + -6.386
-1.2772x = 6 + -6.386

Combine like terms: 6 + -6.386 = -0.386
-1.2772x = -0.386

Divide each side by '-1.2772'.
x = 0.3022236142

Simplifying
x = 0.3022236142

See similar equations:

| .8(1+.5x)=-4 | | 3.5+4.25= | | 48/72 | | f(3)=-16t^2+120t+140 | | 4x-12=8-6x | | f(x)=-16t^2+120t+140 | | (2a+3b-6c)+(5b-4c-a)= | | 6n-22=-14+7n | | (2a+3b-6c)= | | 5ln(x)-3ln(x^2)=-8 | | 8x-13=5+6x | | -16t^2+45=0 | | .4(1+.05x)=-4 | | -16t^2+30=0 | | 5+x=5+x | | Y(x-4)= | | 16t^2+32=0 | | 8/(11y-1)=4/(5y-1) | | 4x-8=x+21 | | -6p=-18 | | 3p+18q=-30 | | v=4/3(3.14)(4^3) | | 5(8+6x)=6x+10 | | 0.5*e^2=0 | | 100/.16= | | w(3w+2)-2w^2+16=w(w+5)-6w+7 | | 100/1/6= | | 14(x^2)-47x+30=0 | | 12x-1-10x=2 | | 105x^2+63x=0 | | n+3(n)=52 | | (18i^12)/(6i^3) |

Equations solver categories